Parapsoriasis – the early stage of primary cutaneous lymphoma? - Roszkiewicz, Jadwiga; Lange, Magdalena; Cegielska, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2010)
The term parapsoriasis describes a group of diseases that at present includes small plaque parapsoriasis (SPP) and large plaque parapsoriasis (LPP). There are some controversies among authors regarding the classification of the above: some recognize them as distinct benign entities, others as the early stage of mycosis fungoides (MF). According to the literature, from 7.5% to 14% of cases of LPP progress to primary cutaneous lymphoma, while SPP is treated as a disorder with no potential of such transformation. Due to confusion about the classification and terminology of parapsoriasis the International Society of Cutaneous Lymphoma introduced, in 2007, a diagnostic algorithm in this group taking into consideration clinical presentation as well as histopathological, immunopathological and molecular features, which enables one to establish a more precise diagnosis and to distinguish among patients with parapsoriasis or early, patch stage of MF those with higher risk of transformation into more advanced stages of the disease.